Explaining listening comprehension among L2 learners of English: The contribution of general language proficiency, vocabulary knowledge and metacognitive awareness. (April 2017) - Wang, Yun; Treffers-Daller, Jeanine
Abstract: Listening comprehension constitutes a major problem for second language learners but little is known about the relative contribution of different factors to listening comprehension. Since there are still only very few studies in this area by comparison with studies focusing on the relationship between reading and vocabulary, there is a need for studies which can fill the gap in our knowledge about the specific contribution of generic and discrete-point measures of language ability to explaining listening. In the present study among 151 non-English major students at a university in Northwest China we explore what proportion of the variance in listening comprehension is explained by general language proficiency, vocabulary size and metacognitive awareness. Our results show that vocabulary size is the strongest predictor, followed by general language proficiency, while metacognitive awareness is less important. We discuss implications for the componential structure of the notion language ability, theories of listening and pedagogical practice in L2 classrooms.